Geography and ecology structure diversification in Ziziphus Mill. (Rhamnaceae) - Rickenback, Jess; Lehmann, Caroline E. R.; Hauenschild, Frank; Hughes, Mark J.; Pezzini, Flávia Fonseca; Pennington, R. Toby (Frontiers of biogeography, 2024)
Understanding the processes responsible for creating and preserving biodiversity within tropical ecosystems is essential for gaining deeper insights into the history, dynamics, and resilience of these environments. We investigated the biogeography and evolution of Ziziphus Mill. (Rhamnaceae), a genus of c.50 species found in all major tropical biomes and across Africa, Asia and Australasia to evaluate how ecology and geography structures its diversification, and their associations with functional traits. We used consistency and retention indices, as well as the delta statistic to test for phylogenetic signal in ecology, geography and functional traits. We constructed a time-calibrated phylogeny using BEAST, followed by the reconstruction of biome and geographical affinities in BioGeoBEARS, and ancestral functional trait evolution using phytools and ape. At a global scale, geography structures Ziziphus’ diversification more than ecology, as evidenced by higher phylogenetic signal in retention indices and the delta statistic. Multiple ecological switches among biomes are associated with dispersal events, which structure Ziziphus’ diversification at smaller scales. Biogeographic estimation suggests that Ziziphus evolved out of closed biomes in Asia during the Oligocene. Long distance dispersal from Asia to Africa resulted in the occupation of two novel biomes, the expanding tropical grassy biome and the desertic biome. Geographic transitions across continents that retain the same biome are fewer but are demonstrated by a dispersal from the closed biome in Asia to the same ecological setting in Australia. In keeping with the younger age of the savanna biome and the Pliocene radiation of geoxylic species, the youngest species in Ziziphus are mostly found in open biomes, and the youngest habit is geoxylic. Leaf hair appears to confer advantages across biomes whilst being a synapomorphy for open and desertic clades. One of two evolutions back into closed biomes is associated with the development of the liana habit. We inferred the most complete phylogeny for Ziziphus to date. Ziziphus originated in closed biomes in Asia in the Oligocene. At a global scale, geography structures diversification more than ecology (biome preference) in Ziziphus . Biome shifts are frequently associated with long distance dispersal events. Shifts in growth form are frequently associated with biome shifts.